Protein Kinase SGK2 Is Induced by the β3 Adrenergic Receptor-cAMP-PKA-PGC-1α/NT-PGC-1α Axis but Dispensable for Brown/Beige Adipose Tissue Thermogenesis - Park, Chul-Hong; Moon, Jiyoung; Park, Minsung; Cheng, Helia; Lee, Jisu; Chang, Ji Suk (Frontiers in Physiology, 2021)
Brown and beige adipocytes are specialized to dissipate energy as heat. Sgk2, encoding a serine/threonine kinase, has been identified as a brown and beige adipocyte-specific gene in rodents and humans; however, its function in brown/beige adipocytes remains unraveled. Here, we examined the regulation and role of Sgk2 in brown/beige adipose tissue thermogenesis. We found that transcriptional coactivators PGC-1α and NT-PGC-1α activated by the β3 adrenergic receptor-cAMP-PKA pathway are recruited to the Sgk2 promoter, triggering Sgk2 transcription in response to cold. SGK2 elevation was closely associated with increased serine/threonine phosphorylation of proteins carrying the consensus RxRxxS/T phosphorylation site. However, despite cold-dependent activation of SGK2, mice lacking Sgk2 exhibited normal cold tolerance at 4C. In addition, Sgk2+/+ and Sgk2-/- mice induced comparable increases in energy expenditure during pharmacological activation of brown and beige adipose tissue with a β3AR agonist. In vitro loss- and gain-of-function studies further demonstrated that Sgk2 ablation or activation does not alter thermogenic gene expression and mitochondrial respiration in brown adipocytes. Collectively, our results reveal a new signaling component SGK2, although dispensable for cold-induced thermogenesis, that adds an additional layer of complexity to the β3AR signaling network in brown/beige adipose tissue.